Reception of The ’Maulid Nabi’ Hadith in the Pangkep Community South Sulawesi (Study of Baku Tradition in Balang Caddi Island) - HS, Muhammad Alwi; Parninsih, Iin (Al-Hikmah, 2022)
This article discusses the reception of hadith as the basis for the Baku tradition in the celebration of the Prophet’s Birthday by the people of Balang Caddi Island. It based on the thesis that in human reception of religious texts there is an informative and performative side. In this context, the hadith of love for the Prophet can be seen from an informative and performative perspective. From an informative point of view, the hadith about the love of the Prophet implies that those who love the Prophet Muhammad will be with the Prophet in Heaven. Meanwhile, from a performative perspective, the community implement the Maulid tradition as was done by the people of Balang Caddi Island. This performative side constantly undergo transmission and transformation from one place and time to another. To understand it, the author makes analytical observations, namely observing and experiencing the celebration of the Baku tradition. The result of this research is that the Birthday of the Prophet among the people of Balang Caddi Island is an effort to maintain the transmission of the values ​​of love to Allah and the Prophet Muhammad in the form of the Baku tradition. As a form of transformation, the Baku tradition in the Prophet’s Birthday among the Community includes the Prophet’s Birthday night at the Darul Dakwah Wal Irsyad School, and the Prophet’s Birthday at the Darus Sa’adah Mosque, as well as the Pabagang context related to the time and form of the Prophet’s Birthday celebration.